1998
DOI: 10.1002/(sici)1096-9136(1998110)15:11<965::aid-dia691>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Cutis/subcutis thickness at insulin injection sites and localization of simulated insulin boluses in children with Type 1 diabetes mellitus: need for individualization of injection technique?

Abstract: The study aimed to describe the variations of cutis/subcutis thickness at insulin injection sites in children with Type 1 diabetes mellitus and to localize the tissue position of a simulated insulin bolus in order to evaluate the need for individualization of injection technique in children. Cutis/subcutis thickness was measured by ultrasound in 47 children (25 girls and 22 boys) without compression (CSCUT) and with compression (CSCT) of the skin at 11 insulin injection sites. Tissue deposition of insulin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 15 publications
1
32
1
Order By: Relevance
“…Birkebaek et al 28 have since showed that in prepubertal children, up to 84% of girls and up to 95% of boys had abdominal skin thickness of < 8 mm. Measurements at the thigh were far more variable depending on the site assessed, and measurements at the buttocks showed a generally higher skin thickness.…”
Section: Needle Lengthmentioning
confidence: 81%
“…Birkebaek et al 28 have since showed that in prepubertal children, up to 84% of girls and up to 95% of boys had abdominal skin thickness of < 8 mm. Measurements at the thigh were far more variable depending on the site assessed, and measurements at the buttocks showed a generally higher skin thickness.…”
Section: Needle Lengthmentioning
confidence: 81%
“…As expected, SCT was directly related to BMI -a change of 10 BMI units accounted for approximately 4 mm change in SCT. Females have greater SCT than males by $5 mm, as has been previously reported 16,19,[29][30][31] . Body site relates to SCT, with the buttocks the thickest.…”
Section: Discussionmentioning
confidence: 99%
“…Note that a standoff was used to optimize image quality by increasing the distance between the transducer and the skin. This method of assessing depth of skin layers has been well-validated previously [7]. …”
Section: Methodsmentioning
confidence: 99%